Harmony search hyper-heuristic with different pitch adjustment operator for scheduling problems / Khairul Anwar ... [et al.] - Anwar, Khairul; A.Awadallah, Mohammed; Al-Betar, Mohammed Azmi (2021)
The Harmony Search Algorithm (HSA) has been adapted in the hyper-heuristics framework as the high-level heuristic named Harmony Search-based Hyper Heuristic (HSHH). Two operators in HSA are used to select and generate a heuristics vector. In this paper the pitch adjustment operator was used in order to enhance the original HSHH. The purpose of applying the pitch adjustment operator was to insert a different way of heuristic selection instead of randomness in memory consideration operator. The effectiveness of the proposed methods was tested with two distinct timetabling and rostering problems. Experimentally, the new HSHH method had improved the original HSHH.